2020
DOI: 10.1007/s11249-020-01364-z
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Dependent Tribological Properties of Bulk Metallic Glasses

Abstract: The macroscale friction and wear properties of the Zr 44 Cu 10 Ni 10 Ti 11 Be 25 metallic glass were investigated as a function of environmental oxygen concentration and contact force. We found remarkably low and predictable friction when both oxidation and frictional heating (that can lead to thermomechanically-driven crystallization) were supressed. Conversely, oxidation and the formation of a mixed metal-oxide layer was shown to increase the friction coefficient while significantly reducing wear rates. Depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…The torsional experiments by Bridgman [223] avoided environmental exposure by using a continuously shearing torsional contact design. With a stable nanocrystalline alloy, where grains at the interface would presumably persist at or close to the same size as those in the bulk, or a bulk metallic glass, where strength is uniform, the friction coefficient would be expected to approach values of, = 1 3 √ 3 ≅ 0.19 ; this was recently experimentally verified with a metallic glass contact at low shear rates in an inert environment, where frictional heating was negligible [224]. Considering the stochastic and often highly variable nature of metals tribological testing, the difference between these two estimates (for nanocrystalline pure metals and alloys) is likely too small to accurately measure, and insignificant from a practical standpoint.…”
Section: Microstructure and Frictionmentioning
confidence: 85%
See 1 more Smart Citation
“…The torsional experiments by Bridgman [223] avoided environmental exposure by using a continuously shearing torsional contact design. With a stable nanocrystalline alloy, where grains at the interface would presumably persist at or close to the same size as those in the bulk, or a bulk metallic glass, where strength is uniform, the friction coefficient would be expected to approach values of, = 1 3 √ 3 ≅ 0.19 ; this was recently experimentally verified with a metallic glass contact at low shear rates in an inert environment, where frictional heating was negligible [224]. Considering the stochastic and often highly variable nature of metals tribological testing, the difference between these two estimates (for nanocrystalline pure metals and alloys) is likely too small to accurately measure, and insignificant from a practical standpoint.…”
Section: Microstructure and Frictionmentioning
confidence: 85%
“…In this situation the energy required to nucleate and move dislocations can exceed the cohesive strength [268], especially along networks of defective zones like grain boundaries. Bulk metallic glasses [264], which can show low friction and wear rate at mild contact stresses, even in inert environments [224], are an interesting limiting case of this effect as they are amorphous and extremely high in strength but have near zero ductility due to their inability to support dislocation nucleation and transport. These novel materials can exhibit extraordinary properties, such as coefficients of restitution of nearly one, so that deformation is nearly entirely elastic until fracture occurs.…”
Section: Routes For Promoting Grain Boundary Sliding In Metalsmentioning
confidence: 99%
“…Tribological behaviors of both types of MGs have been investigated extensively in recent years. Effect of environmental oxygen concentration of the Zr 44 Cu 10 Ni 10 Ti 11 Be 25 MG were investigated [578]. Remarkably low and predictable friction was found when both oxidation and frictional heating were suppressed.…”
Section: Metallic Glasses (Mgs) and Superelastic Metallic Materialsmentioning
confidence: 99%
“…Metallic glasses (MGs) exhibit excellent mechanical properties including extraordinary hardness and strength [1,2]. Thus, MGs have emerged as novel wear-resistant materials with high potential in tribological applications [3][4][5][6][7][8]. Tao et al [3] found that Zr-based MGs present a much smaller friction coefficient than other metals under dry-sliding conditions.…”
Section: Introductionmentioning
confidence: 99%